Analysis of The Efficiency of The Hold Goods Production Process using The Single Minute Exchange of Die (SMED) Method at PT Kencar Sukses Investama - Hamida Asmaul Hasana; Sajiyo Sajiyo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study aims to analyze the efficiency of the HOLD product production process using the Single Minute Exchange of Die (SMED) method at PT Kencar Sukses Investama. The research was conducted because the production process experienced high setup time, machine downtime, and a significant number of HOLD products, which reduced production efficiency and increased operational costs. The study used the Stopwatch Time Study method, Fishbone Diagram analysis, and SMED implementation to identify and reduce non-value-added activities. Data were collected through direct observation, production records, and operator performance assessments involving four production operators. The results showed that the Router process had the highest standard time of 15.38 minutes, while Bokaki reached 12.60 minutes. After SMED implementation, setup efficiency increased by 28.57% for Router and 28.50% for Bokaki. In addition, HOLD products and production costs decreased significantly. Therefore, SMED proved effective in improving production efficiency and reducing production waste.